Report of Frank Balfour-Browne’s collecting in Gran Canaria and Madeira (1932-1933), with the description of Ochthebius (Cobalius) lanthanus sp. nov. (Coleoptera, Hydraenidae) - Ribera, Ignacio; Foster, Garth N. (Zootaxa, 2018)
Ochthebius (Cobalius) lanthanus sp. nov. is described from rockpools in Gran Canaria, based on specimens collected by Professor F. Balfour-Browne in 1932 and newly collected material. The species is morphologically very similar to O. (Cobalius) algicola Wollaston, 1871 from Madeira, but at a genetic distance of ca 10% as measured with the gene cytochrome c oxidase subunit 1. The water beetle collections of Balfour-Browne’s trip to Gran Canaria (1932) and Madeira (1933) are also reported.